Mapping conceptual spaces in contemporary linguistic studies: Insights from lexical analysis - Varvaruk, Inna; Solowij, Ulyana; Stefurak, Roksolana; Ivanyshyn , Nataliia; Dzhochka, Iryna (Research Journal in Advanced Humanities, 2023)
Contemporary linguistic studies have shown an increasing interest in conceptual spaces as a helpful tool for comprehending how meaning is organized and represented. This study focuses on the mapping of abstract areas through lexical analysis techniques. Drawing upon a diverse range of linguistic data, including corpora, dictionaries, and semantic networks, this study explores the interconnectedness of concepts within various domains. Through the identification of co-occurrence patterns and semantic associations, we examined how words and concepts relate to one another in multidimensional spaces. By analyzing the distributional properties and semantic relationships, this research provides beneficial perspicuity into the organization and structure of conceptual spaces, clearing the cognitive processes involved in language comprehension and production. The results offer implications for linguistic domains, including lexical semantics, cognitive linguistics, and natural language processing, emphasizing the potential of mapping conceptual spaces in advancing our understanding of language and cognition. This linguistic study contributes to the growing body of research on conceptual spaces, paving the way for further investigations into the nature of meaning representation and its implications for language acquisition, translation, and computational modeling.